Design of Maximum Power Point Tracking for Solar Collector Drying System: An Experimental Study - Saifuddin M. Jalil; Faizar Abdurrahman; Selamat Meliala; Rosdiana Rosdiana (Institute of Advanced Engineering and Science, 2018)
This research describes the performance of maximum power point tracking as a solar collector of PV system integration for agriculture product drying system. The system comprises of solar collector, tracking PV array, the battery bank, the micro controller and the DC converter. This system is design to enhance the work of solar collector in drying process.. This design is hoped to be an appropriate system in order to ensure the maximum result by providing solar radiation energy. This paper shows the experiment data of the voltage and power response in positioning the PV to yield a maximum photovoltaic array output power of solar drying system device.